PENGEMBANGAN SISTEM DATABASE BERBASIS TRI DARMA PERGURUAN TINGGI PADA PROGRAM STUDI PENDIDIKAN EKONOMI - Tri Nugroho Budi Santoso (Universitas Negeri Malang, 2022)
Abstract: Document management is important for organizations so that documents have good use value. Document management systems are sometimes only run at the parent institution centrally but are not implemented well at low management levels. This research is a development research with a development model design that is used as a reference in this research is the modified Borg and Gall development design. The research subject is the Satya Wacana Christian University undergraduate economic education study program. Data collection techniques using observation, interviews, expert judgment. The instrument used is an interview sheet, observation checklist. expert validation sheets and questionnaires. The results of this study indicate that the Education Database System created has the following feasibility test results: media experts get a rating of 4 in the